Predictors of successful pulmonary valve-sparing repair in pediatric humanitarian patients with Tetralogy of Fallot - Vitor Mendes; Abdelkhalek Mouloudi; Jalal Jolou; Tomasz Nalecz; Ana Abecasis; Telmo Pereira; Tornike Sologashvili (Journal of Cardiothoracic Surgery)
Abstract Introduction The optimal surgical approach for right ventricular outflow tract obstruction in Tetralogy of Fallot aims to preserve the native pulmonary valve annulus, as this is associated with better long-term outcomes. Pediatric humanitarian patients often present with a delayed diagnosis and lack access to preoperative palliative treatments, reducing the likelihood of pulmonary valve annulus preservation and potentially compromising long-term outcomes. This study aims to identify independent predictors of successful pulmonary valve-sparing repair in pediatric humanitarian patients undergoing corrective surgery for Tetralogy of Fallot. Methods Between January 2019 and May 2023, pediatric humanitarian patients with Tetralogy of Fallot underwent surgical correction at our center. We performed a comparative analysis of preoperative, intraoperative, and postoperative variables, followed by univariate and multivariate logistic regression to identify independent predictors of pulmonary valve-sparing repair. Results A lower body mass index (OR = 0.711; p = 0.021; 95% CI = 0.533–0.949), a larger pulmonary valve annulus measured in centimeters (OR = 28.653; p = 0.008; 95% CI = 2.360-347.890) and a higher Z-score of pulmonary valve annulus (OR = 1.606; p = 0.023; 95% CI = 1.067–2.418) were identified as independent predictors of pulmonary valve-sparing repair. Conclusion Successful pulmonary valve-sparing repair was associated with lower BMI and a larger pulmonary valve annulus (both measurements in centimeters and Z-score). These findings may help guide clinical and policy strategies to promote more equitable and effective surgical care in resource-limited settings.